Himalayan tectonics : a modern synthesis - Treloar, P. J.; Searle, M. P. (The Geological Society, 2019)
This volume will provide a profound update of what we know about Himalayan geology today. The text will address issues that range across the fields of tectonics and structural geology to metamorphism, geochronology and sedimentation. This work will be key reading for geoscientists involved in all aspects of orogenic evolution.
Also issued in print: 2019.
Keywords: Plate tectonics -- Himalaya Mountains Region.; Geology, Structural -- Himalaya Mountains Region.; Geology -- Himalaya Mountains Region.; elektronické knihy; electronic books